Histone lysine-specific demethylase 1 regulates the proliferation of hemocytes in the oyster Crassostrea gigas - Gu, Xiaoyu; Qiao, Xue; Yu, Simiao; Song, Xiaorui; Wang, Lingling; Song, Linsheng (Frontiers in Immunology, 2022)
Lysine specific demethylase 1 (LSD1) is an essential epigenetic governor of haematopoietic differentiation, which can specifically mono-methylated H3K4 (H3K4me1) and di-methylated H3K4 (H3K4me2) as a transcriptional co-repressor. Here, a conserved LSD1 (CgLSD1) with a SWIRM domain and an amino oxidase (AO) domain was identified from the Pacific oyster Crassostrea Gigas. The mRNA transcripts of CgLSD1 were widely expressed in oyster tissues with the highest level in mantle (80.40-fold compared to that in gills, p < 0.05). During the ontogenesis, the mRNA transcripts of CgLSD1 were ubiquitously expressed with the highest expression level at early D-veliger larvae stage (10.00-fold compared to that in Zygote, p < 0.05). In haemocytes after Vibrio splendidus stimulation, the mRNA expression level of CgLSD1 was significantly down-regulated at 3, 6, 24, and 48 h with the lowest level at 3 h, which was 0.15-fold compared to that in Seawater group (SW group), (p < 0.05). Immunocytochemical analysis displayed that CgLSD1 was mainly distributed in nucleus of haemocytes. After the protein expression level of CgLSD1 was knocked down by RNAi (0.17-fold compared to that in dsEGFP group, p < 0.05), the H3K4me1 and H3K4me2 methylation level in haemocyte protein was significantly increased, which was 1.89-fold and 2.51-fold compared to that in dsEGFP group (p < 0.05), respectively. In the dsLSD1 group, the percentage of haemocytes with EdU positive signals in the total circulating haemocytes were significantly increased after V. splendidus stimulation, which was 2.73-fold compared to that in dsEGFP group (p < 0.001). Furthermore, the mRNA expression level of potential granulocyte markers CgSOX11 and CgAATase increased significantly (2.60-fold and 1.26-fold compared to that in the dsEGFP group respectively, p < 0.05), while the mRNA transcripts of potential agranulocyte marker CgCD9 were decreased significantly (0.71-fold compared to that in dsEGFP group, p < 0.05). Meanwhile, in dsLSD1 group, the mRNA expression level of oyster cytokine-like factor CgAstakine was increased significantly (3.52-fold compared to that in dsEGFP group, p < 0.05). The above results demonstrated that CgLSD1 was a conserved member of lysine demethylate enzyme to regulate haemocyte proliferation during haematopoietic process.